Mengembangkan Kemampuan Anak Dalam Mengenal Konsep Bilangan menggunakan Model Talking Stick Dan Media Kantong Pintar Pada Anak Kelompok B TK Putera 1 Banjarbaru - Anisa, Pitri; Sjamsir, Hasbi (Manajemen Pendidikan Program Doktor, 2020)
This research is motivated by the child ability to recognize the concept of number has not yet developed as expected. This is due to monotonous learning activities, lack of use of active, innovative and fun learning modelsand media for children and more teacher centered learni This study aims to describe the cognitive development of children in recognizing the number concept usiang a of Talking Stick and media smart pouch. This type of research is classroom action research. The research subjects were children in group B TK Putera 1 Banjarbaru in 2020/2021 semester. That cognitive development uses a combination Explicit Instruction, Make A Match and Talking Stick models that can develop children’s ability to recognize number carousel.